2013
DOI: 10.1093/ndt/gft292
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the pre-transplant histological score on 3-year graft outcomes of kidneys from marginal donors: a single-centre study

Abstract: In our experience, provided the donor has a normal renal function, a difference in the pre-transplant histological score of kidneys from marginal cadaveric donors do not have a significant influence on the outcome 3 years after transplantation. Our findings might represent a basis for designing a randomized controlled trial of using a higher histological score threshold for the DKT allocation of grafts from ECDs with a normal renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 25 publications
4
15
0
1
Order By: Relevance
“…Our study confirms and expands previous evidence that histological criteria for allocation of marginal kidneys to single transplantation can be widened to include grafts with a score of 4 (31-33). Since those grafts represented almost 20% of the kidneys that underwent pre-transplant biopsy evaluation in our cohort, our results could have major implications in further expanding the pool of available donors.…”
Section: Discussionsupporting
confidence: 88%
“…Our study confirms and expands previous evidence that histological criteria for allocation of marginal kidneys to single transplantation can be widened to include grafts with a score of 4 (31-33). Since those grafts represented almost 20% of the kidneys that underwent pre-transplant biopsy evaluation in our cohort, our results could have major implications in further expanding the pool of available donors.…”
Section: Discussionsupporting
confidence: 88%
“…Despite a high allograft recovery rate reported in highest risk donors, kidneys with the highest KDPI score might have superior outcomes with a lower RS (<4) than those with a higher RS score (RS = 4) . In our analysis, our single‐center results of PTDB show a lower discard rate (19.8%) for the highest KDPI group and marginal kidneys with a RS of 4 allocated to single transplantation did not show lower graft or patient survival, previously described by other studies . Our study also shows that the use of a relatively low threshold (RS ≀ 4) appears to be safe for single kidney transplantation and identifies good organs from donors with several risk factors that would otherwise be rejected.…”
Section: Discussionsupporting
confidence: 60%
“…Four of eight studies reported an association with GF , while four others did not find an association with GF . Of three studies that 0 used morphometry to quantitate chronic injury, two reported an association with GF , while one did not .…”
Section: Resultsmentioning
confidence: 88%
“…Ortiz et al showed a correlation between CADI score and serum creatinine at 6 months and 2 years, but not at 1 year. However, four other studies found no association between histologic scores and graft function .…”
Section: Resultsmentioning
confidence: 90%